La norma constitucional e infraconstitucional sobre la transgresión del derecho a la cercanía familiar de las personas privadas de la libertad en el sistema penitenciario. - Ortega, Miguel A. (2022)
This scientific article aims to analyze the conditions of deprivation of liberty in relation to Human Rights and some aspects about these conditions where violation of rights is displayed, specifically when a person deprived of liberty is transferred from one prison to another, limiting to the fact that the individualized rehabilitation plan cannot be carried out, and even more, it causes that a correct rehabilitation of the person deprived of liberty is not carried out, since he does not have his family for the rehabilitation, a fundamental situation as unconditional support to have effective results, in order to enforce the provisions of Article 12, number 13 of the Comprehensive Criminal Organic Code, in accordance with Article 35 of the Constitution of the Republic of Ecuador, as a priority care group. The methodology used is the qualitative approach, the type was feasible at an explanatory level, its purpose was to explain the behavior of one variable as a function of another, a cause- effect relationship was proposed when determining its critical points. The results showed deficiencies in the prison system, as well as arbitrariness in the transfer of persons deprived of liberty, as well as violation of constitutional rights.